NOTION OF MEANS OF SECURING THE OBLIGATIONS IN MODERN CIVIL LAW OF THE RUSSIAN FEDERATION - Trezubov, Egor (Revista Inclusiones, 2020)
At the modern stage of development of the Russian civil law, the practice of the obligation relations uses the means of securing the obligations, which are directly enshrined in the law, as well as nonnamed means, which are aimed at “strengthening” the legal relationship, the additional protection of the rights and interests of a creditor. Many means of securing the obligations, which are named in the Civil Code of the Russian Federation and other laws, are not forming a proper institutional system, they differ in an effect of influencing the debtor and other persons as well as in the functional purpose. Because of poor condition of a contractual discipline in the country the creditors have to implement in the legal practice the different function-oriented means of protecting their rights, and even additional measures of operative influence, which are often called non-named means of securing the obligations in the literature. Within this research, by means of dialectical and system-structured methods of the research, and a functional-analytic method, in order to reveal the general characteristics a comprehensive analysis of the means of securing the obligations is conducted in order to reveal the general characteristics of such a legal institution. A conclusion is drawn that the means of securing the obligation can be only an accessory obligation, which is functionally aimed at strengthening the creditor’s position by means of providing it additional property, procedural guarantees or a performance substitute in the event of the debtor’s default in the basic obligation.